El Retorno de las Biguanidas: Metformin - Poma, Augusto (1996)
Here, we present a brief historical background and address the importance of the use of metformin in the treatment of non-insulin dependent diabetes mellitus, based in the european and canadian experience. We recommended a dose of 500 mg, because there has been showed that the incidence of lactic acidosis is very low, a good dose completion is reached, and it can be combined with other oral antidiabetic drugs.